Complex and divergent histories gave rise to genome‐wide divergence patterns amongst European whitefish (Coregonus lavaretus). (26th October 2021) - Crotti, Marco; Bean, Colin W.; Gowans, Andy R. D.; Winfield, Ian J.; Butowska, Magdalena; Wanzenböck, Josef; Bondarencko, Galina; Præbel, Kim; Adams, Colin E.; Elmer, Kathryn R.
Abstract: Pleistocene glaciations dramatically affected species distribution in regions that were impacted by ice cover and subsequent postglacial range expansion impacted contemporary biodiversity in complex ways. The European whitefish, Coregonus lavaretus, is a widely distributed salmonid fish species on mainland Europe, but in Britain it has only seven native populations, all of which are found on the western extremes of the island. The origins and colonization routes of the species into Britain are unknown but likely contributed to contemporary genetic patterns and regional uniqueness. Here, we used up to 25, 751 genome‐wide polymorphic loci to reconstruct the history and to discern the demographic and evolutionary forces underpinning divergence between British populations. Overall, we found lower genetic diversity in Scottish populations but high differentiation ( F ST = 0.433–0.712) from the English/Welsh and other European populations. Differentiation was elevated genome‐wide rather than in particular genomic regions. Demographic modelling supported a postglacial colonization into western Scotland from northern refugia and a separate colonization route for the English/Welsh populations from southern refugia, with these two groups having been separated for more than ca . 50 Ky. We found cyto‐nuclear discordance at a European scale, with the Scottish populations clustering closely with Baltic population in the mtDNA analysis but not in the nuclear data, and with the Norwegian and Alpine populations displaying the same mtDNA haplotype but being distantly related in the nuclear tree. These findings suggest that neutral processes, primarily drift and regionally distinct pre‐glacial evolutionary histories, are important drivers of genomic divergence in British populations of European whitefish. This sheds new light on the establishment of the native British freshwater fauna after the last glacial maximum. Abstract : Using a dataset of genome‐wide polymorphic loci and population genomics approaches, we reconstructed the evolutionary history and discerned the demographic and evolutionary forces underpinning divergence between British populations of European whitefish. We found a deep divergence between Scottish and English/Welsh populations, with the latter sharing a more recent common ancestor with populations from central Europe.